2
$\begingroup$

Problem

Simplify logaritm:

$$ \log_{e^2}(e^{4a}+ae^{4a}) $$

preferably in a way that end result contains only natural logarithm.

Attempt to solve

I know few computational rules about logarithms:

$$ \log_a(xy) = \log_a(x)+\log_a(y) $$

$$ \log_a(\frac{x}{y})=\log_a{x}-\log_a(y) $$

$$ \log_a(x^n)=n\log_a(x) $$

And formula for change of basis :

$$ \log_a(x)=\frac{\log_b(x)}{\log_b(a)} $$

There is sum inside this logarithm and it appears we don't have formula for this. On wikipedia i found two formulas about summation / substraction inside logarithm:

$$ \log_b(a+c)=\log_b a+ \log_b (1+\frac{c}{a}) $$

$$ \log_b(a-c)=\log_b a+ \log_b (1-\frac{c}{a}) $$

I have no former experience / knowledge of these formulas but for now the assumption is these are correct.

I would try to first try change of basis to $\log_{e^2}()\rightarrow \log_e() = \ln()$

$$ \log_{e^2}(e^{4a}+ae^{4a})=\frac{\log_e(e^{4a}+ae^{4a})}{\log_e(e ^2)} $$

$$ \log_{e}(e^{4a}+ae^{4a})=\log_{e^2}(e^{4a}+ae^{4a})\cdot \log_e({e^2}) $$

$$ \log_{e}(e^{4a}+ae^{4a})=2 \cdot \log_{e^2}(e^{4a}+ae^{4a})$$

We get the original logarithm with base $e$

$$ \log_{e^2}(e^{4a}+ae^{4a})=\frac{1}{2}\ln(e^{4a}+ae^{4a}) $$

Now the sum:

$$ \frac{1}{2}\ln((a+1)e^{4a}) $$

$$4a \frac{1}{2} \ln ((a+1)e) $$ $$ 4a \cdot \frac{1}{2} \ln (a+1) + \ln(e) $$

$$ \frac{4a}{2} \ln {(a+1)} + 1 $$

$$ 2a \ln (a+1) + 1 $$

If there is an error let me know.

$\endgroup$
1
$\begingroup$

Your answer is good, except for a slip in the second equation after your words “Now the sum”, because the exponent $4a$ does not apply to the factor $(1+a)$. But as usual when we’re beginners, there’s often a shorter, clearer way.

There are two questions here, the first of which is how to handle the unorthodox $\log_{e^2}$, while the second is how to handle the sum inside the parentheses.

For the first question, I recommend not depending on formulas that may seem to come from on high, but rather going back to the definitions: \begin{align} \log_b(x)=L\qquad&\text{means}\qquad b^L=x\\ \log_{e^2}(x)=Y\qquad&\text{means}\qquad (e^2)^Y=x&\text{so}\qquad e^{2Y}=x\\ \log_e(x)=2Y\qquad&\text{means}\qquad e^{2Y}=x&\text{so}\qquad Y={\scriptstyle\frac12}\log_e(x)\,. \end{align} That solves the first question: $\log_{e^2}(e^{4a}+ae^{4a})=\frac12\ln(e^{4a}+ae^{4a})$.

The second question now becomes easy: again, don’t rely on that funny rule from Wikipedia, but just factor the $e^{4a}$ from the two terms: $\frac12\ln(e^{4a}+ae^{4a})=\frac12\ln\bigl(e^{4a}(1+a)\bigr) =\frac12\bigl(\ln(e^{4a})+\ln(1+a)\bigr)$. Now remember that $\ln(e^{4a})=4a$ and get your answer $2a+\frac12\ln(1+a)$.

$\endgroup$
1
$\begingroup$

Factorizing the numerator and using change of basis :

$$\frac{\ln ((a+1)e^{4a})}{\ln e^2} =\frac 12 (\ln{(a+1)}+\ln e^{4a})$$ $$= \frac 12\ln{(a+1)} +2a$$

$\endgroup$
1
$\begingroup$

Using $$\log_{a}(x) = \frac{\ln(x)}{\ln(a)},$$ where $\ln(x) = \log_{e}(x)$, then \begin{align} \log_{e^{2}}(e^{4 a} + a e^{4 a}) &= \frac{\ln(e^{4 a}(1+a))}{\ln(e^{2})} \\ &= \frac{4 a + \ln(1 + a)}{2 \, \ln(e)} \\ &= 2 a + \frac{\ln(1+a)}{2}. \end{align}

Since $$ \frac{\ln(1 +a)}{2} = \frac{\ln(1+a)}{2 \, \ln(e)} = \frac{\ln(1+a)}{\ln(e^{2})} = \log_{e^{2}}(1+a),$$ then $$\ln_{e^{2}}(e^{4 a} + a e^{4 a}) = 2a + \log_{e^{2}}(1+a).$$

$\endgroup$
1
$\begingroup$

You were doing fine down to $$\frac 12\ln((a+1)e^{4a})$$ but then you cannot pull out the $4a$ because it is not an exponent on $a+1$. Instead you should do $$\frac 12\ln((a+1)e^{4a})=\frac 12\left(\ln (a+1)+\ln(e^{4a})\right)\\=\frac 12\ln(a+1)+2a$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.